2003
DOI: 10.1074/jbc.m207920200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions of Yeast Frequenin (Frq1) with the Phosphatidylinositol 4-Kinase Isoform, Pik1

Abstract: Recognition that phosphoinositides and inositol phosphates are key regulators of many processes in eukaryotic cells has brought increased attention to the enzymes that regulate the synthesis and turnover of these molecules (reviewed in Refs. 1-3). Of particular interest are the enzymes responsible for producing the various polyphosphoinositides situated on the cytosolic face of cellular membranes, which initiate several different signaling pathways by serving as highly specific recognition determinants for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 57 publications
5
50
0
Order By: Relevance
“…The NCS-1 used for our experiments was not myristoylated, and the previous study suggested that myristoylation was required. It should be noted that the homologous interaction between yeast proteins is not dependent on myristoylation of Frq1 (49). Although a genetic interaction between ARF and Pik1 has been inferred in yeast (8) mammalian ARF1 has been demonstrated to recruit a PI(4)K␤ activity to isolated Golgi membranes (6) and to increase activity of PI(4)K␤ (50), no evidence for a direct physical interaction between the two proteins has thus far been provided.…”
Section: Discussionmentioning
confidence: 99%
“…The NCS-1 used for our experiments was not myristoylated, and the previous study suggested that myristoylation was required. It should be noted that the homologous interaction between yeast proteins is not dependent on myristoylation of Frq1 (49). Although a genetic interaction between ARF and Pik1 has been inferred in yeast (8) mammalian ARF1 has been demonstrated to recruit a PI(4)K␤ activity to isolated Golgi membranes (6) and to increase activity of PI(4)K␤ (50), no evidence for a direct physical interaction between the two proteins has thus far been provided.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, frequentin is an neuronal calcium sensor protein that binds to the phosphatidylinositol 4-kinase isoform, Pik1. In this case, hydrophobic residues within a 28-residue peptide from Pik1 (residues 145-172) form an amphipathic helical binding site for frequentin (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…ts strains show greatly distorted and exaggerated Golgi membranes, vacuole fragmentation, and defective actin polarization at the budding pole (64,1655 (672). The Golgi recruitment of Pik1p is also controlled by Arf1, and the enzyme also interacts with the Arf1 exchange factor Sec7 (512).…”
Section: Pik1mentioning
confidence: 99%